2002
DOI: 10.1016/s0304-3959(02)00269-5
|View full text |Cite
|
Sign up to set email alerts
|

Does acupuncture improve the orthopedic management of chronic low back pain – a randomized, blinded, controlled trial with 3 months follow up

Abstract: This prospective, randomised controlled trial, with three parallel groups, patient and observer blinded for verum and sham acupuncture and a follow up of 3 months raises the question: "Does a combination of acupuncture and conservative orthopedic treatment improve conservative orthopedic treatment in chronic low back pain (LBP). 186 in-patients of a LBP rehabilitation center with a history of LBP >or=6 weeks, VAS >or=50mm, and no pending compensation claims, were selected; for the three random group 4 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 20 publications
0
153
0
6
Order By: Relevance
“…The percentage of patients showing a ≥50% reduction of pain was significantly greater in group b) than both in groups a) and c), although there were no differences in mobility (Schober's sign and finger to ground distance) nor in the intake of diclofenac (Molsberger et al 2002).…”
Section: Systematic Reviewsmentioning
confidence: 64%
“…The percentage of patients showing a ≥50% reduction of pain was significantly greater in group b) than both in groups a) and c), although there were no differences in mobility (Schober's sign and finger to ground distance) nor in the intake of diclofenac (Molsberger et al 2002).…”
Section: Systematic Reviewsmentioning
confidence: 64%
“…[73][74][75][76] The design and patient populations in these trials make direct comparison with the present results difficult: two trials did not assess traditional acupuncture 73,74 and a third excluded patients with a history of less than 6 months of back pain. 76 The fourth trial, a three-arm open trial of traditional acupuncture, massage and self-care, by Cherkin and colleagues, was closest to the present study in design.…”
Section: Clinical Outcomesmentioning
confidence: 82%
“…For simplicity, each comparison was treated as an individual trial. Trials reported on the following categories of interventions: acupuncture (10 trials) [25,42,73,74,85,95,99,104,106,128], back school (2 trials) [11,28], behavioural (7 trials) [10,21,62,111,130,132,133], electrotherapy (20 trials) [8, 15, 25, 27, 37, 49-51, 54, 57, 63, 69, 76, 77, 89, 94, 107, 122, 137, 143], exercise (10 trials) [29,37,43,48,50,59,67,116,131,136], heatwrap therapy (2 trials) [109,110], insoles (1 trial) [127], magnets (1 trial) [33], massage (1 trial) [116], neuroreflexotherapy (1 trial) [93] [16,117,129]. Trial characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%